2007
DOI: 10.1016/j.neuroimage.2007.04.058
|View full text |Cite
|
Sign up to set email alerts
|

Functional MRI with active, fully implanted, deep brain stimulation systems: Safety and experimental confounds

Abstract: We investigated safety issues and potential experimental confounds when performing functional magnetic resonance imaging (fMRI) investigations in human subjects with fully implanted, active, deep brain stimulation (DBS) systems. Measurements of temperature and induced voltage were performed in an in vitro arrangement simulating bilateral DBS during magnetic resonance imaging (MRI) using head transmit coils in both 1.5 and 3.0T MRI systems. For MRI sequences typical of an fMRI study with coil-averaged specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
94
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 101 publications
(98 citation statements)
references
References 41 publications
4
94
0
Order By: Relevance
“…Different applications may require different levels of field accuracy in specific locations. An accurate assessment of the electromagnetic field inside the phantom is important when evaluating SAR levels as overall safety of the patient [9][10][11][12][13][14][15][16] or the RFinduced heating in patients with conductive medical devices that are fully implanted in the body [22] like deep brain stimulators [8,17,18] or pacemakers [1,20,21]. Conversely, an accurate representation of ||E ⃗ || in the space between the coil and the load is important when evaluating safety in patients with conductive medical devices that are partially implanted or in contact with the skin [7,23].…”
Section: Discussionmentioning
confidence: 99%
“…Different applications may require different levels of field accuracy in specific locations. An accurate assessment of the electromagnetic field inside the phantom is important when evaluating SAR levels as overall safety of the patient [9][10][11][12][13][14][15][16] or the RFinduced heating in patients with conductive medical devices that are fully implanted in the body [22] like deep brain stimulators [8,17,18] or pacemakers [1,20,21]. Conversely, an accurate representation of ||E ⃗ || in the space between the coil and the load is important when evaluating safety in patients with conductive medical devices that are partially implanted or in contact with the skin [7,23].…”
Section: Discussionmentioning
confidence: 99%
“…A Perspex phantom, similar to one described previously [19,23], which broadly follows the ASTM standard for testing passive implants [34] was formed with a shape and dimensions approximating those of an adult human torso (Figure 1). This was filled to a depth of approximately 10cm with a semi-liquid gel comprising distilled water, poly-acrylic acid partial sodium salt (Aldrich Chemical) (8g/litre) and sodium chloride (0.70 g/litre) with electrical (conductivity of 0.26 Sm -1 ) and thermal characteristics (limited convection) similar to those of human tissue [34,35].…”
Section: Methodsmentioning
confidence: 99%
“…Combinations of these have been previously studied in the context of scalp EEGfMRI [18] and active deep brain stimulation (DBS) during MRI [19][20][21][22][23][24]. Depending on their frequency and amplitude, excessive currents in tissue may cause electro-motive forces, electrolysis, depolarisation and stimulation, burning, coagulation, and vaporisation which can all lead to cell damage and ultimately cell death [25][26][27].…”
mentioning
confidence: 99%
“…82 The study was performed at 1.5T and 3T by using head-transmit coils. The authors showed that for fMRI sequences with coil-averaged SARs Ͻ0.4 W/kg, MR imagingϪinduced temperatures were less than measurement sensitivity (0.1°C) at 1.5T and Ͻ0.5°C at 3T.…”
Section: 77mentioning
confidence: 99%